Vocal cord paralysis appears to be an acquired lesion in children with repaired esophageal atresia/tracheoesophageal fistula. (September 2018) - Kovesi, Thomas; Porcaro, Federica; Petreschi, Francesca; Trozzi, Marilena; Bottero, Sergio; Cutrera, Renato
Abstract: Objectives: Determine whether vocal cord paresis or paralysis (VCP/P) following surgical repair of congenital esophageal atresia/tracheoesophageal fistula (EA/TEF) is generally a primary anomaly, or is secondary to EA/TEF repair. Methods: We carried out a retrospective study based on a recently published protocol, which included the systematic performance of a laryngo-tracheo-bronchoscopy before and after EA/TEF repair. Results: There were 105 patients with EA/TEF referred for multidisciplinary follow-up, between 2010 and 2015. Sixty-four of the 105 patients included in the study underwent EA/TEF repair at the referral center and had pre-operative bronchoscopy; the others had their initial surgery elsewhere. No included patient had VCP/P detected pre-operatively. Six patients (4 initially managed at the referral center) were diagnosed with VCP/P during the follow-up period (6/105, 5.7%). Conclusion: VCP appears to be an acquired lesion in this population.